A refined temporal framework for newly discovered fossil assemblages of the upper Cedar Mountain Formation (Mussentuchit Member), Mussentuchit Wash, Central Utah. (June 2020) - Tucker, Ryan T.; Zanno, Lindsay E.; Huang, Hui-Qing; Makovicky, Peter J.
Abstract: Detangling the pace and structure of biotic turnover between the late Early and early Late Cretaceous within the Western Interior of North America requires refined stratigraphic controls of fossiliferous sediments; however, to date, many key mid-Cretaceous strata remain understudied and only tenuously or coarsely correlated. Intensified data collection in the uppermost Cedar Mountain Formation (Mussentuchit Member) suggests preservation of an understudied volcanilithic archive that can provide key insight into this enigmatic period in North America's geological history. Here we utilize detrital zircon geochronology (coupling LA-ICP-MS and CA-TIMS) to contextualize the sedimentary history of the Mussentuchit Member within the region of Mussentuchit Wash, Central Utah and compare these data with previous approaches. This study finds that emplacement of contemporaneous volcanilithics occurred in two distinct phases. The first phase occurred no older than 96 Ma, and a subsequent younger phase occurred no older than 94 Ma. Secondly, this study finds preliminary evidence that both eruptions occurred within a westerly lying arc; however, it is evident that these represent different volcanic inliers and terranes. Finally, this study also finds that the Mussentuchit Member can be reliably subdivided into two informal lower and upper sub-members, with the potential to preserve two distinct, previously unified fossil assemblages. Our data provides both a refined localized framework for newly uncovered fossil assemblages within this particular Mussentuchit Wash depo-centre and serves to strengthen correlations between mid-Cretaceous strata across the Western Interior. Graphical abstract: Image 1 Highlights: Chronostratigraphic framework for newly discovered fossils in the area of Mussentuchit Wash, Utah. Mussentuchit Member (Cedar Mountain Formation) was emplaced over ±2 myr period, from 96 to 94 Ma. Identification of coeval and non-coeval volcanism and sedimentation. Possible subdivision of the Mussentuchit Member into distinct lower and upper sub-members. Identification of different source terranes in the western lying arc.